Blended Learning Melalui Google Classroom: Studi Kasus di Universitas Islam Negeri Sultan Syarif Kasim Riau - Risnawati; Musa Thahir (Lembaga Anotero Scientific Pekanbaru, 2020)
The Indonesian government has instructed the use of information and communication technology-based learning processes, especially internet-based learning. However, there are still weaknesses in the use of internet-based learning in the learning process among students. Therefore, this article aims to describe the use of blended learning through Google Classroom and determine the effect of applying blended learning through Google classroom in supporting the learning of Educational Research Statistics. The research method used in this article is a quantitative descriptive study sample of PAI UIN Suska Riau study program students. To obtain primary data from the field, questionnaires and tests are used to measure student learning outcomes. After each data is collected and tabulated, the data will be analyzed using statistical parametric analysis with descriptive tests and multiple regression tests using SPSS Version 23.00. The results showed that: 1) Student acceptance of the ease of Google Classroom had no positive effect in supporting learning of Research Methodology; 2) The performance of Google Classroom has a positive effect in supporting learning of Research Methodology; 3) Students' expectations for the use of Google Classroom do not have a positive effect in supporting learning of Research Methodology; and 4) Social Influence on the use of Google Classroom has no positive effect in supporting learning of Research Methodology.